Outcomes and surgical complications following living‐donor renal transplantation using kidneys retrieved with trans‐peritoneal or retro‐peritoneal hand‐assisted laparoscopic nephrectomy. Issue 12 (27th October 2020) - Favi, Evaldo; Iesari, Samuele; Catarsini, Nivia; Sivaprakasam, Rajesh; Cucinotta, Eugenio; Manzia, Tommaso; Puliatti, Carmelo; Cacciola, Roberto
Abstract: The best minimally invasive procedure for living‐donor kidney retrieval remains debated. Our objective was to assess trans‐peritoneal (TP) and retro‐peritoneal (RP) hand‐assisted laparoscopic donor nephrectomy (HALDN). In this single‐center retrospective study, we analyzed results from 317 living‐donor renal transplants (RT) performed between 2008 and 2016. Donor and recipient outcomes were compared between TP‐HALDN (n = 235) and RP‐HALDN (n = 82). Conversion to open nephrectomy (0.4% vs 0%; P = 1.000), intra‐operative complications (1.7% vs 1.2%; P = 1.000), and 1‐year overall post‐operative complications (11.9% vs 17.1%; P = .258) rates were similar in TP‐HALDN and RP‐HALDN. Overall surgical site infections were higher in RP‐HALDN (6.1% vs 1.7%; P = .053), whereas incisional hernias were only recorded following TP‐HALDN (3.4% vs 0%; P = .118). The duration of the procedure was 11‐minute shorter for TP‐HALDN than RP‐HALDN ( P < .001) but extraction time was equivalent (2, IQR 1.5‐2.5 minutes; P = 1.000). RT following TP‐HALDN and RP‐HALDN showed comparable one‐year death‐censored allograft survival (97% vs 98.8%; P = .685), primary non‐function (0.4% vs 0%; P = .290), delayed graft function (1.3% vs 4.9%; P = .077), and urological complications (2.6% vs 4.9%; P = .290) rates. In our series, donor and recipient outcomes were not substantially affected by the approach used for donor nephrectomy. TP‐HALDN and RP‐HALDN were both safe and effective.